ONLINE SHOPPING MOTIVES AND BEHAVIORAL INTENTIONS: MODERATING EFFECTS OF AGE AND FREQUENCY OF ONLINE SHOPPING - Fadhilah Zainal Abidin; Mastura Roni; Siti Hajar Mohamad (International Journal of Accounting, Finance and Business, 2022)
This study attempts to examine the role of hedonic and utilitarian antecedents ofbehavior on behavioral intention and encompasses age and frequency of online shopping asmoderator variables to further evaluate the association among online shopping motives andbehavioral intention in the context of online food delivery during Covid-19 pandemic inMalaysia. The study seeks to measure perceived usefulness, internal subjective, externalsubjective and hedonic motivation on predicting the behavioral intention amongst online fooddelivery customers on behavioral intention. The descriptive survey research design was utilizedfor this study. The target population was the online food delivery customers during Covid-19pandemic in Malaysia. By using a convenient sampling technique, 135 sample participantswere selected from the target population. The reliability scales were tallied by usingCronbach’s Alpha. The findings of the study are gleaned by using regression to investigate therole online shopping motives towards behavioral intention and whether age and frequency ofshopping moderated the association between online shopping motives and behavioral intention.Through Statistical Package of Social Science (SPSS), Hayes process was used regarding themoderation effect. The main results of regression analysis validated that perceived usefulness,perceived ease of use and normative motives have a significant and positive effect on onlinepurchase behavior intentions compared to hedonic motivation. Specifically, the study suggeststhat frequency of online shopping significantly moderates the perceived usefulness on thebehavioral intention amongst online food delivery consumers during the pandemic.